Allocation of General and Administrative Expenses. - Wright, Howard W. (The Accounting Review, 1966)
This article considers the conceptual problem of allocating general and administrative expenses. It seems clear that a production-related base is more acceptable to government auditors than any other. This is justified where a significant portion of the general and administrative expenses are production-generated. However, where the pool includes little, if any, production-generated expenses any base which is representative of the year's activity should be acceptable. In addition, the article includes recommendations which may help in solving practical problems in allocating administrative expenses.